2014
DOI: 10.1038/hortres.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of ethylene and jasmonate mediated defense response in apple (Malus domestica) root during Pythium ultimum infection

Abstract: Apple replant disease (ARD) is a significant economic restraint to the successful re-establishment of new apple orchards on sites previously planted to the same crop. Pythium ultimum, an oomycete, is a significant component of the ARD pathogen complex. Although ethylene (ET)- and jasmonic acid (JA)-mediated defense responses are intensively studied in the foliar pathosystem, the transferability of this knowledge to the interaction between a perennial root system and soilborne pathogens is unknown. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 38 publications
3
36
0
1
Order By: Relevance
“…ET/JA modulated defense responses during interaction between apple roots and P. ultimum were also studied by a recent candidate gene based approach [23]. Our data demonstrated that many DEGs associated with ET/JA biosynthesis and signal transduction were activated during the interaction between apple roots and P. ultimum.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…ET/JA modulated defense responses during interaction between apple roots and P. ultimum were also studied by a recent candidate gene based approach [23]. Our data demonstrated that many DEGs associated with ET/JA biosynthesis and signal transduction were activated during the interaction between apple roots and P. ultimum.…”
Section: Discussionmentioning
confidence: 73%
“…The investigation of the molecular interaction between plant root and soilborne pathogens has lagged considerably behind foliar pathosystems. The molecular defense response in apple roots in response to the infection by ARD pathogens has rarely been explored [23]. A transcriptomic approach can offer the genome-wide view of the molecular regulation networks underlying the defense responses in apple root tissue towards soilborne ARD pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…94 hormone metabolism (Shin et al, 2014(Shin et al, , 2016Zhu et al, 2014). Comparative transcriptomic studies of roots of the sensitive rootstock M26 grown either in ARD or gamma irradiated ARD soils revealed several differences in the expression of genes involved in stress responses (Weiß et al, 2017a, b).…”
Section: Plant Reactions To Ardmentioning
confidence: 99%
“…The sequences of the amplified regions seem to be identical between these two cultivars using qRT-PCR method. The internal reference of an apple MdActin (MDP0000752428) has been used in several previous studies and its consistency among various tissue types and treatments has been tested in several studies [54]- [56]. Additionally, use of "adaptive calibrator" for calculating the relative expression values enhances the comparability of the relative gene expression levels between two cultivars.…”
Section: Identified Auxin Efflux Carrier and Iaa-amido Synthetase Genmentioning
confidence: 99%